Gonzalo grabs the good life - Levy, Janice; Slavin, Bill (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2009)
Gonzalo the rooster wins the lottery and leaves his job on the farm to search for a better life, but no matter what he does or where he goes, Gonzalo feels as though something is missing.
2.0
K-3
Keywords: Roosters -- Juvenile fiction; Wealth -- Juvenile fiction; Roosters -- Fiction; Wealth -- Fiction; Roosters -- Fiction; Wealth -- Fiction